2018
DOI: 10.1007/s10648-018-9432-z
|View full text |Cite
|
Sign up to set email alerts
|

A Heuristic Framework of Spatial Ability: a Review and Synthesis of Spatial Factor Literature to Support its Translation into STEM Education

Abstract: An abundance of empirical evidence exists identifying a significant correlation between spatial ability and educational performance particularly in science, technology, engineering and mathematics (STEM). Despite this evidence, a causal explanation has yet to be identified. Pertinent research illustrates that spatial ability can be developed and that doing so has positive educational effects. However, contention exists within the relevant literature concerning the explicit definition for spatial ability. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 112 publications
2
59
0
1
Order By: Relevance
“…Thus, teaching experiences carried out with engineering students revealed that an improvement of both the acquired knowledge and spatial visualization skill are achieved by using a VT. This is in agreement with previous studies [15][16][17][18][19][20] where it was demonstrated that the visualization skill can be improved through appropriate training. Taking all the previously mentioned into account, two facts can be stated: (i) the graphical design of any Didactic Virtual Tool (DVT) is a key factor in achieving an educative aim; and (ii) in the case that such a tool is used for solving any spatial visualization problem, the tool design becomes an even more influential factor.…”
Section: Introductionsupporting
confidence: 93%
“…Thus, teaching experiences carried out with engineering students revealed that an improvement of both the acquired knowledge and spatial visualization skill are achieved by using a VT. This is in agreement with previous studies [15][16][17][18][19][20] where it was demonstrated that the visualization skill can be improved through appropriate training. Taking all the previously mentioned into account, two facts can be stated: (i) the graphical design of any Didactic Virtual Tool (DVT) is a key factor in achieving an educative aim; and (ii) in the case that such a tool is used for solving any spatial visualization problem, the tool design becomes an even more influential factor.…”
Section: Introductionsupporting
confidence: 93%
“…Significant research has been conducted to create a meaningful intervention to achieve this aim (Sorby 2009;Veurink and Sorby 2011). However, it is imperative that the assumption is not made that such an impasse can only occur in students deemed to have low levels of spatial ability as denoted by performance on the PSVT:R. Spatial ability is widely understood as a second order cognitive factor encompassing multiple 1st order factors (Buckley et al 2018;Carroll 1993;Schneider and McGrew 2012). The PSVT:R is posited to measure the spatial relations factor.…”
Section: Discussionmentioning
confidence: 99%
“…What constitutes good spatial skills? Since its earliest conceptualization 8 , spatial ability has been considered a multifaceted construct comprising several related, yet separable, skills 9 . One of the most widely adopted definitions of spatial ability describes it as the ability to generate, retain, retrieve, and transform wellstructured visual images 10 .…”
Section: Introductionmentioning
confidence: 99%